The praxis of nursing in the process of health education - de Sousa, Karinna Alves Amorim (Seven Editora, 2023)
This article presents reflections on the praxis of nursing in the context of health education, in the light of Paulo Freire’s approaches. Considering great importance as a way to achieve health promotion and quality of life, from the appreciation of the experiences of the subjects, their personal demands and social challenges. It is noticed, in this analysis, that the work of the nurse contributes immensely to the realization of the process of health education, as a way of promoting the health and quality of life of individuals. Health education requires from the nurse an engaged, aware, liberated, autonomous, able and qualified professional to implement in a coherent way the process of emancipation, autonomy and attitudes necessary for the promotion of health and quality of life of people. DOI:https://doi.org/10.56238/alookdevelopv1-183